Answer:
9x^2-9x-3
Step-by-step explanation:
3x*3x=9x^2
3x*-4=-12x
1*3x=3x
1*-4=-3
9x^2-12x+3x-3
9x^2-9x-3
The formula is L = 2 pi r * (angle measure / 360). We have everything we need to solve this, the angle is 90 and the radius is 12: L = 2 pi (12) (90/360). Do the work inside the parenthesis first to get : L = 2 pi (12)(.25). Solving for L: L = 6pi
Answer:
f(-1)=6×(-1)^-4=6/(-1)^4=6/1=6
Answer:
x = -3
Step-by-step explanation:
![x-2+3=-2\\x+1=-2\\x=-3](https://tex.z-dn.net/?f=x-2%2B3%3D-2%5C%5Cx%2B1%3D-2%5C%5Cx%3D-3)